Acessibilidade universal aplicada ao patrimônio cultural edificado: estudo das condições de acessibilidade em uma rota interligando bens culturais no Centro de Fortaleza/Ce - Melo, Clarissa Fonseca Azevedo de (2023)
The act of moving is part of people's everyday lives, whether it's inside a house, taking a walk to a nearby supermarket, the commute from home to work, or to a recreational space. The means to carry out this activity should be accessible to ensure equal opportunities for everyone, including people with disabilities and reduced mobility. The objective of this research is analyzing a pre-established route in downtown Fortaleza that links culturally and historically significant landmarks, with the purpose of evaluating the accessibility conditions along this route, both in the surrounding areas and within these cultural sites. The Centro neighborhood in Fortaleza represents the historical site where the city's urban and economic development started. It includes several historical structures that have been assigned specific functions in order to preserve these valuable assets. Ensuring accessibility within these buildings is essential to promote equal opportunities for all individuals to access the cultural significance held within these locations. Moreover, the routes leading to these buildings must adhere to accessibility norms. In order to carry out this research, a section of the Post- Occupancy Evaluation methodology, as outlined by Rheingantz et al. (2009), using methods such as exploratory Walkthrought and visual mapping; and the methodology for diagnosing accessibility in urban centers based on Cohen et al., (2013), using the Post Occupancy assessment method, with the application of checklists, photographic survey and route mapping. As a result of the accessibility conditions on the route and the cultural assets evaluated, some aspects are highlighted that are erroneously repeated in the sections analyzed, both in those with older paving and those that have undergone renovations, such as the application of tactile signage on adjacent floors shaking; some points in accordance with the accessibility standard and many others that require adjustments.